Community Transformation in Early Detection of Head and Neck Cancer in Bali - Sagung Agung Putri Dwiastuti; IGAA Dharmawati (Health Gate, 2026)
Cancer is the second leading cause of death worldwide and the leading cause of death in Indonesia. One type of cancer that causes a large number of deaths in Indonesia is head and neck cancer. In Indonesia, the prevalence of head and neck cancer is quite high, with an incidence of 4.7 per 100,000 population. The purpose of this study is to determine the community's knowledge, attitudes, and behaviors regarding head and neck cancer. A cross-sectional study was conducted in the working area of the Community Health Center in Bali, with a cadre population spread across eight villages. Samples were taken using the Slovin formula with a total of 70 respondents, using simple random sampling. The type of analysis used was Spearman's correlation test. The results obtained showed that the majority of respondents were female, 54.3%, with the highest level of education being a bachelor's degree, 51.4%. The highest level of knowledge was good, 48.6%, and the majority of respondents stated that knowledge about head and neck cancer was very important, 88.6%. Bivariate analysis using Spearman's correlation test to examine the relationship between the three components of knowledge, attitude, and behavior showed a significant relationship between behavior and knowledge (p<0.05). It can therefore be concluded that there is a significant relationship between knowledge and behavior and values (p<0.05).